Androgenetic alopecia: Clinical features and trichoscopy - Shashank Bansod; Aseem Sharma; Madhulika Mhatre (Clinical Dermatology Review, 2022)
Androgenetic alopecia, known alternatively as male pattern baldness when men are affected, and female pattern hair loss, when it affects women, is a form of alopecia characterized by miniaturization – a process wherein thick, long terminal hair are converted to short, thin, miniaturized hair due to the effect of dihydrotestosterone. Various pathogenetic mechanisms exist that support the process. Due to the unusually high disease burden and the psychosocial affliction, a lot of research in underway in the field. Clinically, this subtype of patterned hair loss presents with typical and atypical patterns presenting with thinning of hair and / or balding, or both. It is of paramount importance to recognize and grade the disease early to administer appropriate therapy. Trichoscopy also plays a major role in diagnosing, prognosticating and even monitoring patient response to therapy.